Psychological impacts of the COVID-19 epidemic on Chinese people: Exposure, post-traumatic stress symptom, and emotion regulation - Jiang, Hong-juan; Nan, Jiang; Lv, Zhi-yue; Yang, Juan (Asian Pacific journal of tropical medicine, 2020)
Objective: To examine the effects of coronavirus disease-2019 (COVID-19) exposure, expressive suppression/cognitive reappraisal, and demographic variables on post-traumatic stress symptoms (PTS) among Chinese.Methods: Participants were recruited by social media through WeChat and 6049 Chinese (aged from 17 to 63 years; median=24) from 31 provinces were included in the study. PTS symptoms, expressive suppression, and cognitive reappraisal were assessed after the outbreak of COVID-19. A regression mixture analysis was conducted in Mplus 7. Results: A regression mixture model identified three latent classes that were primarily distinguished by differential effects of COVID- 19 exposures on PTS symptoms: (1) Class 1 (mildly PTS symptoms, 80.9％), (2) Class 2 (moderate PTS symptoms, 13.0％), and (3) Class 3 (high PTS symptoms, 6.1％). The results demonstrated that the young, women and people with responsibilities and concerns for others were more vulnerable to PTS symptoms; and they had more expression inhibition and less cognitive reappraisal in three latent classes. Conclusions: The findings suggest that more attention needs to be paid to vulnerable groups such as the young, women and people with responsibilities and concerns for others. Therapies to encourage emotional expression and increase cognitive reappraisal may also be helpful for trauma survivors.